2022
DOI: 10.3389/fsurg.2022.874113
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Vascular Surgery Presence in Bilibili Video Platform of China

Abstract: BackgroundWith the development of the Internet, more and more patients search for disease-related information on video platforms during the treatment process, and physicians also look for learning materials through these video platforms. Bilibili is one of the most popular video platforms in China. This study evaluated information on various interesting topics, and related surgical procedures searched through Bilibili.MethodThe Bilibili platform was independently queried for 12 common vascular diseases or rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The total number of videos on Bilibili (n = 6154) far exceeded that of the other two platforms (1884 videos on Toutiao, 2105 videos on TikTok). Current research suggested that websites on the rst search results page receive almost 95% of web tra c, leaving only 5% for remaining search results pages [30]. Our results con rmed the importance of the rst-page results after retrieval.…”
Section: Major Ndingsupporting
confidence: 75%
See 1 more Smart Citation
“…The total number of videos on Bilibili (n = 6154) far exceeded that of the other two platforms (1884 videos on Toutiao, 2105 videos on TikTok). Current research suggested that websites on the rst search results page receive almost 95% of web tra c, leaving only 5% for remaining search results pages [30]. Our results con rmed the importance of the rst-page results after retrieval.…”
Section: Major Ndingsupporting
confidence: 75%
“…The total DISCERN score was calculated by summing up scores over questions 1-15. All videos were divided into ve categories based on their total DISCERN score: very poor (< 27), poor (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), fair (39-50), good (51-62), and excellent (63-75). JAMA benchmark criteria were used to evaluate online health information reliability, including four criteria (authorship, attribution, disclosure, and currency).…”
Section: Methodsmentioning
confidence: 99%
“…Bilibili also implements strict regulations and restrictions for videos published on their platform, adhering to national regulations on the management of network information. In contrast, TikTok and Kwai do not adhere as closely to national regulations [ 21 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the platform statistics, TikTok had over 600 million daily active users on March 31, 2021 [ 19 ], and Kwai had over 308 million daily active users on December 31, 2021, on average [ 20 ]. Bilibili is a platform that publishes entertainment and educational videos [ 21 ] and had a comparatively low average number of daily active users—over 72.2 million on December 31, 2021 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, the exponential growth of short video platforms has captured significant academic interest. Research has primarily focused on the information quality and credibility of health-related content (K. Chen et al 2022;Enver et al 2020;Li et al 2020), factors influencing the perceived usefulness of short health videos (Campbell and Rudan, 2020), viewing behaviors of specific videos by different demographics (Rosenthal et al 2021), and content analyses focusing on communication characteristics and strategies (Han et al 2022;Wu et al 2022;Yurdaisik, 2020). However, the specific health information needs within the short video context remain underexplored.…”
Section: Introductionmentioning
confidence: 99%